Comorbidity in hospitalized patients with schizophrenia - Videnova, Vilma; Stefanovski, Branislav; Manusheva, Nensi (Elsevier, 2018)
Introduction.– There is an insufficient awareness of comorbidity in schizophrenia on the part of patients, caregivers, health care providers, and researchers. Comorbidity has often been underrecognized and underdiagnosed in psychiatric patients, especially among those with schizophrenia. Objective.– The aim of this study is to analyze comorbidity in hospitalized patients with schizophrenia. Methods.– Medical charts of 96 inpatients with schizophrenia (42 male and 54 female, aged 19-65) were retrospectively analysed in terms of comorbidity. Results.– Comorbid substance abuse was found in 17 patients, 7 patients had personality disorders, while 34 had anxiety disorders. Conclusions.– Comorbid substance abuse leads to poorer medication compliance, higher rates of rehospitalization, poorer adjustment and treatment response in schizophrenia patients. Increased likelihood of violent behaviour and greater use of emergency services are also associated with substance abuse in schizophrenia. Comorbidity has negative impact on treatment outcome in schizophrenia patients which affects the prospects of discharge in this patients and their quality of life Disclosure of interest.– The authors have not supplied their declaration of competing interest.